2022
DOI: 10.1210/clinem/dgac550
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical Features of Post-COVID-19 Vaccination Early-onset Graves’ Disease

Abstract: Context Several case reports of Graves’ disease (GD) occurrence after COVID-19 vaccination were recently published and possibly related to the autoimmune syndrome induced by adjuvants (ASIA). The aim of our study was to evaluate possible distinctive features in the presentation and clinical course of patients with GD occurring early (within 4 weeks) after COVID-19 vaccination who attended our Endocrine Unit in 2021. Design Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…Another study, focusing on early-onset GD within 4 weeks of COVID-19 vaccination, revealed distinctive features in this patient group, such as an older age at onset, a higher prevalence of males, and an initially favorable response to treatment [13].…”
Section: Occurrence Of Sat After Sars-cov-2-vaccinationmentioning
confidence: 85%
“…Another study, focusing on early-onset GD within 4 weeks of COVID-19 vaccination, revealed distinctive features in this patient group, such as an older age at onset, a higher prevalence of males, and an initially favorable response to treatment [13].…”
Section: Occurrence Of Sat After Sars-cov-2-vaccinationmentioning
confidence: 85%
“…In this case, we report a case of suspected Graves’ disease due to COVID-19 vaccination with a good response to thiamazole, but TRAb was still positive one year later. Although Graves’ disease following COVID-19 vaccination has been reported [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], few reports have presented data on the chronic phase of Graves’ disease after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Under such circumstances, although the COVID-19 mRNA vaccine was developed and administered worldwide, various adverse effects have been reported, including cardiovascular diseases such as acute coronary syndrome (ACS) and myocarditis [ 2 , 3 , 4 ], and hyperthyroidism including Graves’ disease, Graves’ orbitopathy, subacute thyroiditis, and silent thyroiditis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other exclusion criteria were: age less than 18 years, pregnancy, history of thyroid disease or previous thyroid surgery, concomitant medications known to interfere with thyroid function (lithium, amiodarone, interferon-α and antiretroviral drugs), severe kidney insufficiency (eGFR < 30 ml/min), and severe liver failure. Patients’ enrollment took place between 2 May and 31 July 2020, before availability of SARS-CoV-2 vaccines, to avoid potential biases due to occurrence of post-vaccination thyroid disorders ( 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%